2016
DOI: 10.3892/etm.2016.3465
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPK attenuates LPS-induced acute lung injury by upregulation of PGC1α and SOD1

Abstract: Abstract. Evidence suggests that an imbalance between oxidation and antioxidation is involved in the pathogenesis of acute lung injury/acute respiratory distress syndrome (ALI/ARDS). Activation of AMP-activated protein kinase (AMPK) has been shown to inhibit the occurrence of ALI/ARDS. However, it is unknown whether activation of AMPK benefits ALI/ARDS by restoration of the oxidant and antioxidant balance, and which mechanisms are responsible for this process. The present study aimed to address these issues. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 22 publications
(28 reference statements)
3
32
0
Order By: Relevance
“…Taken together, these data demonstrate a beneficial effect of AMPK activation in younger mice, greater than that in older mice, and suggest that the AICAR's beneficial effects were a result of AMPK activation, rather than off-target effects. This work extends the similar prior findings of the role of AMPK in LPS-induced lung injury (7,8) to hemorrhage-induced lung injury.…”
Section: Impaired Ampk Activity Drives Age-associated Acute Lung Injusupporting
confidence: 88%
“…Taken together, these data demonstrate a beneficial effect of AMPK activation in younger mice, greater than that in older mice, and suggest that the AICAR's beneficial effects were a result of AMPK activation, rather than off-target effects. This work extends the similar prior findings of the role of AMPK in LPS-induced lung injury (7,8) to hemorrhage-induced lung injury.…”
Section: Impaired Ampk Activity Drives Age-associated Acute Lung Injusupporting
confidence: 88%
“…A recent study has reported that the level of PGC‐1α was reduced in a murine model of ALI . In our current study, ALI mouse model was established by injection of LPS to explore the potential roles of PGC1α/HSF1 and its underlying molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, AL treatment decreased the MDA content. SOD is an important antioxidant that can eliminate the harmful byproducts of cellular metabolisms, such as free radicals . Our results indicated that AL treatment increased SOD levels over those observed in the untreated LPS‐injured group.…”
Section: Discussionmentioning
confidence: 53%